Biosugar Production from Gracilaria verrucosa with Sulfamic Acid Pretreatment and Subsequent Enzymatic Hydrolysis - Park, Mi-Ra; Kim, Sung-Koo; Jeong, Gwi-Taek (Biotechnology and bioprocess engineering, 2018)
In this study, sulfamic acid-catalyzed pretreatment and subsequent enzymatic hydrolysis was conducted to produce biosugar from the marine macro-alga Gracilaria verrucosa . Sulfamic acid has dual active sites and is a green catalyst. Optimized sulfamic acid pretreatment at 130°C with 7.5% biomass and 100 mM sulfamic acid for 90 min yielded 39.9% total reducing sugar (TRS). Subsequent enzymatic hydrolysis yielded 69.1% TRS. These results indicate the potential of sulfamic acidcatalyzed pretreatment and subsequent enzymatic hydrolysis in producing biosugars using a biorefinery process.